Images of conflict - Walters, Huw Talfryn; Indus Films ([Cardiff, Wales, UK] : Indus Films, 2010)
Images of conflict looks at the work of seven war photographers from visions of conflict in Vietnam to the current battles in Iraq. Photojournalists tell their stories of life in war zones, trying to make photo stories with one eye on survival and another eye on producing strong, truthful images with a narrative
Executive producer BBC worldwide, Mark Reynolds ; editor, Madoc Robert
Narrated by Aneirin Hughes
Keywords: War photography; War photographers